2018
DOI: 10.1002/ppul.24179
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in a cohort of 5‐year‐old children born very preterm

Abstract: Objective We assessed lung function and respiratory health in an area‐based prospective cohort of preschool children born very preterm. Design Lung function was measured by interrupter respiratory resistance (Rint) and forced oscillation technique (FOT) (respiratory resistance (Rrs8), reactance (Xrs8), and area under the reactance curve (AX)) at a median age of 5.2 years in a cohort of 194 children born at 22‐31 weeks of gestational age (GA) in Tuscany, Italy. Respiratory symptoms and hospitalizations were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…Even late preterm birth has been shown to affect lung function later in life [36,37]. At a functional level, clinical experiments with forced oscillation techniques comparable to those used in this paper, showed worse results in former preterm infants compared to term controls [38,39]. In general, pre-and postnatal factors (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…Even late preterm birth has been shown to affect lung function later in life [36,37]. At a functional level, clinical experiments with forced oscillation techniques comparable to those used in this paper, showed worse results in former preterm infants compared to term controls [38,39]. In general, pre-and postnatal factors (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…It has been con rmed that premature birth can cause immature lung, low lung function, immature immune system function, thereby increasing the risk of wheezing in children [11][12][13][14]. Enrico Lombard et al showed that GA and the development of the lung were closely related [15]. In this study, included newborns were grouped and compared by GA, and the results con rmed that newborns with younger GA were at higher risk of early wheezing, which was consistent with the study of Unal et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been con rmed that premature birth can lead to immature lungs, low lung function, and immature immune system function, thereby increasing the risk of wheezing in children [11][12][13][14]. Enrico Lombard et al showed that GA and the development of the lung were closely related [15]. In this study, included newborns were grouped and compared by GA, and the results con rmed that new-borns with a younger GA were at higher risk of early wheezing, which was consistent with the study of Unal et al [16].…”
Section: Discussionmentioning
confidence: 99%